Thermochromic ink for inkjet printing and its preparation method and application
By constructing a solvent rapid absorption layer in inkjet printing thermochromic inks and using polymerized Ni-based thermochromic complexes, the problems of unclear imaging of inks on the glass surface and poor rheology of inorganic pigments are solved, and clear imaging and process simplification are achieved.
Patent Information
- Application Number
- CN202411747374.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The inkjet printing thermochromic inks is not imaged clearly on the glass surface, and the rheology performance of inorganic pigments is poor, resulting in complex inkjet printing process, uneven pigment settlement and color distribution.
By building a solvent rapid absorption layer, the problem of difficulty in ink solvent absorption is solved, and the rheology regulation of ink is achieved through polymerized Ni-based thermochromic complexes and polymer-based thermochromic pigments.
It realizes clear imaging of ink on the glass surface, solves the rheology problem of inorganic pigments, simplifies the inkjet printing process, and improves the dispersion uniformity and stability of pigments.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ink preparation, relates to inkjet printing thermochromic ink, and also relates to a method for preparing the inkjet printing thermochromic ink. Background Art
[0002] Thermochromic ink is a kind of ink with thermochromic properties. It can change color rapidly with the change of ambient temperature, making the colored object have a dynamic color effect. Therefore, it is widely used in food anti-counterfeiting labels and heat-sensitive packaging materials. Among them, inorganic thermochromic pigments are the more commonly used thermochromic materials. People combine thermochromic pigments with fillers, solvents, additives, etc. These ingredients are evenly mixed and repeatedly rolled to form a viscous gel-like ink, which prints patterns and texts on the substrate. Inkjet printing thermochromic ink not only places high demands on substrates and inks.
[0003] For printing substrates, traditional printing substrates are mostly paper, which has a good ink absorption effect. However, when the substrate is glass, the glass cannot absorb or volatilize the solvent in the ink as quickly as possible, which will lead to unclear imaging. In the face of this problem, a common method is to first apply a pre-treatment coating with solvent absorption performance on the surface of these substrates and then inkjet print. The ink absorption and color fixation effect of the coating will make the printed effect equivalent to that of paper printing, but this type of pre-printing leads to a complex inkjet printing process, and the pre-treatment coating required for different substrates is inconsistent. At the same time, for inks, inorganic pigments have poor rheological properties and cannot be used for inkjet printing, and the particle size is large during synthesis. Mechanical grinding is usually used in the use of inks. After grinding, the particle size becomes smaller, which changes the optical properties of the ink and is difficult to control. It is inevitable that there are a few large-particle inorganic pigments, which lead to pigment sedimentation, uneven color distribution, and clogging of the inkjet needle. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing thermochromic ink for inkjet printing, which solves the problem of difficult ink solvent absorption by constructing a solvent rapid absorption layer, and at the same time, the method can achieve rheological control of the ink.
[0005] Another object of the present invention is to provide an inkjet printable thermochromic ink.
[0006] The first technical solution adopted by the present invention is a method for preparing a thermochromic ink for inkjet printing, which specifically comprises the following steps:
[0007] Step 1, preparing a polymerizable Ni-based thermochromic complex;
[0008] Step 2, preparing a polymer-based thermochromic pigment based on the product obtained in step 1;
[0009] Step 3, preparing a polymer-based thermochromic ink based on the product obtained in step 2.
[0010] The first technical solution of the present invention is also characterized in that:
[0011] The specific process of step 1 is:
[0012] Step 1.1, add 5-10 mL of acetylacetone to 10-15 mL of tetrahydrofuran solution, then add 1-2 g of sodium carbonate and stir for 15-30 min, then add 4-8 g of 4-vinylbenzyl chloride, and separate through a column to obtain styryl acetylacetone;
[0013] Step 1.2, add 1-2 g of styryl acetylacetone, 0.7-1.4 g of nickel nitrate, 0.8-1.6 mL of N, N, N'-trimethylethylenediamine and 1.5-3 g of sodium tetraphenylborate to 20-40 mL of ethanol solution, stir evenly, then add 20-40 mL of 3-6 mol / L sodium carbonate aqueous solution, stir at room temperature for 20-40 min, then filter to obtain a red filter cake, and wash it three times with 100-200 mL of deionized water, 45-60 o C for 12-24 hours to obtain a red monomer, i.e., a polymerizable Ni-based thermochromic complex monomer.
[0014] The specific process of step 2 is:
[0015] Take 3-6g of polymerizable Ni-based thermochromic complex monomer and add it to 10-20mL of tetrahydrofuran solution, then add 6-12mL of butyl acrylate, 4-8mL of glycidyl acrylate, and 0.3-0.6mL of triacrylate glycerol in sequence, stir evenly, add 20-30mg of azobisisobutyronitrile, and heat to 65-80℃ under nitrogen atmosphere. o C for 6-12h. After the reaction, pour the reaction solution directly into 100-200mL of industrial alcohol to quench the reaction and precipitate to obtain a red powder. Continue to wash it with 100-200mL of industrial alcohol for 3 times to obtain a polymer-based thermochromic pigment.
[0016] The specific process of step 3 is: take 2-4g of polymer-based thermochromic pigment, 5-10mL of ethylene glycol ethyl ether and 0.5-1g of starch, add them into a grinder and grind for 10-20 min to obtain a gel-like ink, continue to add 5-10mL of ethylene glycol ethyl ether solvent and 0.12-0.24g of triphenylmethane triisocyanate, stir evenly to obtain a polymer-based thermochromic ink.
[0017] The second technical solution adopted by the present invention is that the inkjet printing thermochromic ink is prepared by adopting the above-mentioned preparation method of the inkjet printing thermochromic ink.
[0018] The third technical solution adopted by the present invention is that the inkjet printing thermochromic ink is used for spraying on the glass.
[0019] The third technical solution of the present invention is also characterized in that:
[0020] Before spraying ink on the glass, an absorbent layer must first be sprayed on the glass surface.
[0021] The preparation process of the absorption layer is as follows: 2-4 g of polyethylene glycol ethyl ether ester modified nano calcium carbonate, 0.2-0.4 mL of acrylic acid, 0.5-1 mL of acrylic acid-(di)-ethylene glycol ethyl ether ester and 3-6 mL of ethanol are added into a grinder and ground for 10-20 minutes to obtain a gel ink, and 3-6 mL of ethanol solvent and 5-10 mg of azobisisobutyronitrile are added to obtain a mixed solution; the mixed solution is sprayed on the glass surface with a thickness of 10-20 μm, and finally irradiated with a 45-60 W ultraviolet lamp for 10-15 seconds to obtain the obtained solution.
[0022] The preparation process of polyethylene glycol ether ester modified nano calcium carbonate is as follows:
[0023] Take 5-10g of nano calcium carbonate and add it to 50-100mL of ethylene glycol ether solvent, stir for 30-60min, and use ultrasonic dispersion instrument with power of 200-400W to ultrasonically disperse for 15-30min to obtain nano calcium carbonate dispersion liquid; heat the nano calcium carbonate dispersion liquid to 60-80 o C, and add 2-3g of 3-(trimethoxysilyl)propyl methacrylate dropwise to the dispersion, the addition time is 15-30min, and the reaction is continued for 30-60min. After the reaction is completed, cool to room temperature, centrifuge at 7000-10000r / min, and remove the supernatant; wash the precipitate with 50-100mL of ethylene glycol ether and centrifuge, repeat three times, and place in an oven at 65-80 o C drying for 12-24 h, the obtained olefin siloxane modified nano calcium carbonate powder; 3-6 g of olefin siloxane modified nano calcium carbonate powder was dispersed in N, N-dimethylformamide solution, stirred for 30-60 min, ultrasonically dispersed for 15-30 min using a 200-400 W ultrasonic disperser, and then 2-4 mL of acrylic acid-(di)-ethylene glycol ethyl ether ester, 0.3-0.6 mL of acrylic acid and 20-40 mg of azobisisobutyronitrile were added to the solution, and heated to 65-80° C under nitrogen protection. oC for 3-6 hours, after cooling to room temperature, add 200-400 mL of industrial alcohol to quench the reaction and precipitate the product, wash with 50-100 mL of industrial alcohol, centrifuge, repeat three times, and obtain polyethylene glycol ethyl ether ester modified nano calcium carbonate.
[0024] The beneficial effects of the present invention are as follows:
[0025] 1. The present invention constructs an organic metal polymer material, and utilizes the change and combination of monomer structural units to achieve the tuning of ink rheology. The polymer skeleton inhibits the crystallization of the complex to form large-grained crystals, and can only form an amorphous polymer material. The problem of ink solvent absorption is solved by constructing a solvent rapid absorption layer.
[0026] 2. The present invention introduces pigment molecules into the polymer skeleton by polymerization to obtain an organic metal polymer material, which can achieve the regulation of the rheology and nanometer size of the ink, and solves the problems of physical mixing of inorganic pigments, which leads to uniform dispersion of pigments in the solvent, easy sedimentation, and clogging of the inkjet needle. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is the ultraviolet absorption spectra of Example 1 of the present invention and Comparative Examples 1-6 at room temperature. DETAILED DESCRIPTION
[0028] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0029] The method for preparing the thermochromic ink for inkjet printing of the present invention specifically comprises the following steps:
[0030] Step 1, preparation of a polymerizable Ni-based thermochromic complex, specifically:
[0031] Take 5-10mL of acetylacetone and add it to 10-15mL of tetrahydrofuran solution, add 1-2g of sodium carbonate and stir for 15-30min, then add 4-8g of 4-vinylbenzyl chloride and separate through a column to obtain styryl acetylacetone. Take 1-2g of styryl acetylacetone, 0.7-1.4g of nickel nitrate, 0.8-1.6mL of N, N, N'-trimethylethylenediamine and 1.5-3g of sodium tetraphenylborate and add them to 20-40mL of ethanol solution respectively, stir evenly and then add 20-40mL of 3-6mol / L sodium carbonate aqueous solution. Stir at room temperature for 20-40min, then filter to obtain a red filter cake, and wash it three times with 100-200mL of deionized water, 45-60 o C for 12-24 hours to obtain a red monomer, i.e., a polymerizable Ni-based thermochromic complex.
[0032] Step 2, preparation of polymer-based thermochromic pigment, specifically:
[0033] Take 3-6g of polymerizable Ni-based thermochromic complex monomer, add it to 10-20mL of tetrahydrofuran solution, then add 6-12mL of butyl acrylate, 4-8mL of glycidyl acrylate, and 0.3-0.6mL of glycerol triacrylate, stir evenly, add 20-30mg of azobisisobutyronitrile, and heat to 65-80℃ under nitrogen atmosphere. o C for 6-12 hours. After the reaction is completed, the reaction solution is directly poured into 100-200 mL of industrial alcohol to quench the reaction and precipitate to obtain a red powder, which is then washed repeatedly with 100-200 mL of industrial alcohol for 3 times to obtain a polymer-based thermochromic pigment.
[0034] Step 3, preparation of polymer-based thermochromic ink, specifically:
[0035] Take 2-4g of polymer-based thermochromic pigment, 5-10mL of ethylene glycol ethyl ether and 0.5-1g of starch, add them into a grinder and grind for 10-20 min to obtain a gel-like ink, continue to add 5-10mL of ethylene glycol ethyl ether solvent and 0.12-0.24g of cross-linking agent triphenylmethane triisocyanate, stir evenly to obtain a polymer-based thermochromic ink.
[0036] The ink is placed in an inkjet printer and sprayed on the glass surface containing the fast absorbing layer.
[0037] The preparation process of the fast absorption layer is as follows:
[0038] Take 2-4g of polyethylene glycol ethyl ether modified nano calcium carbonate, 0.2-0.4mL of acrylic acid, 0.5-1mL of acrylic acid-(di)-ethylene glycol ethyl ether and 3-6mL of ethanol, add them into a grinder and grind for 10-20 min to obtain a gel-like ink, then continue to add 3-6mL of ethanol solvent and 5-10mg of azobisisobutyronitrile, spray the mixed solution on the glass surface with a thickness of 10-20um, and finally irradiate with a 45-60W ultraviolet lamp for 10-15s to obtain the ink.
[0039] The preparation process of polyethylene glycol ether ester modified nano calcium carbonate is as follows:
[0040] Take 5-10 g of nano calcium carbonate and add it to 50-100 mL of ethylene glycol ether solvent, stir for 30-60 min, and further use a 200-400 W ultrasonic disperser to ultrasonically disperse for 15-30 min to obtain a nano calcium carbonate dispersion. Heat the nano calcium carbonate dispersion to 60-80 oC, and add 2-3g of 3-(trimethoxysilyl) propyl methacrylate dropwise to the nano calcium carbonate dispersion for 15-30min. Continue the reaction for 30-60min after the addition is complete. After the reaction is complete, cool to room temperature, centrifuge at 7000-10000r / min using a high-speed centrifuge, and remove the supernatant. Wash the precipitate with 50-100mL of ethylene glycol ether, centrifuge, repeat three times, and place in an oven at 65-80 o C and dried for 12-24 h to obtain olefin siloxane modified nano calcium carbonate powder. Take 3-6 g of olefin siloxane modified nano calcium carbonate powder and disperse it in 10-20 mL of N,N-dimethylformamide solution, stir for 30-60 min, and further use a 200-400 W ultrasonic disperser to ultrasonically disperse for 15-30 min, then add 2-4 mL of acrylic acid-(di)-ethylene glycol ethyl ether ester, 0.3-0.6 mL of acrylic acid and 20-40 mg of azobisisobutyronitrile to the solution, and heat to 65-80 °C under nitrogen protection. o C for 3-6 hours, cool to room temperature, add 200-400 mL of industrial alcohol to quench the reaction and precipitate the product, wash with 50-100 mL of industrial alcohol, centrifuge, repeat three times, and obtain polyethylene glycol ethyl ether ester modified nano calcium carbonate.
[0041] Example 1
[0042] Step 1, preparation of a polymerizable Ni-based thermochromic complex, specifically:
[0043] Take 5mL of acetylacetone and add it to 10mL of tetrahydrofuran solution. Add 1g of sodium carbonate and stir for 15min. Then add 4g of 4-vinylbenzyl chloride and separate through a column to obtain styryl acetylacetone. Take 1g of styryl acetylacetone, 0.7g of nickel nitrate, 0.8mL of N, N, N'-trimethylethylenediamine and 1.5g of sodium tetraphenylborate and add them to 20mL of ethanol solution respectively. Stir evenly and then add 20mL of 3mol / L sodium carbonate aqueous solution. Stir at room temperature for 20min, then filter to obtain a red filter cake, and wash it three times with 100mL of deionized water, 45 o C for 12 h to obtain a red monomer, i.e., a polymerizable Ni-based thermochromic complex.
[0044] Step 2, preparation of polymer-based thermochromic pigment, specifically:
[0045] Take 3g of polymerizable Ni-based thermochromic complex monomer and add it to 10mL of tetrahydrofuran solution. Then add 6mL of butyl acrylate, 4mL of glycidyl acrylate and 0.3mL of glycerol triacrylate and stir evenly. Then add 20mg of azobisisobutyronitrile and heat to 65℃ under nitrogen atmosphere.o C for 6 hours. After the reaction, the reaction solution was directly poured into 100 mL of industrial alcohol to quench the reaction and precipitate to obtain a red powder, which was then washed three times with 100 mL of industrial alcohol to obtain a polymer-based thermochromic pigment.
[0046] Step 3, preparation of polymer-based thermochromic ink, specifically:
[0047] Take 2g of polymer-based thermochromic pigment, 5mL of ethylene glycol ethyl ether and 0.5g of starch, add them into a grinder and grind for 10min to obtain a gel-like ink, then continue to add 5mL of ethylene glycol ethyl ether solvent and 0.12g of cross-linking agent triphenylmethane triisocyanate, stir evenly to obtain a polymer-based thermochromic ink.
[0048] The ink is placed in an inkjet printer and sprayed on the glass surface containing the fast absorbing layer.
[0049] The preparation process of the fast absorption layer is as follows:
[0050] Take 2g of polyethylene glycol ethyl ether modified nano calcium carbonate, 0.2mL of acrylic acid, 0.5mL of acrylic acid-(di)-ethylene glycol ethyl ether and 3mL of ethanol, add them into a grinder and grind for 10 min to obtain a gel ink, then continue to add 3mL of ethanol solvent and 5mg of azobisisobutyronitrile, and spray the mixed solution on the glass surface with a thickness of 10um. Finally, 45W ultraviolet lamp is used for irradiation for 10s.
[0051] Wherein, the preparation process of polyethylene glycol ether ester modified nano calcium carbonate is:
[0052] Take 5 g of nano calcium carbonate and add it to 50 mL of ethylene glycol ether solvent, stir for 30 min, and further use 200 W ultrasonic disperser to ultrasonically disperse for 15 min to obtain nano calcium carbonate dispersion. o C, and add 2g of 3-(trimethoxysilyl) propyl methacrylate dropwise to the dispersion for 15min. Continue the reaction for 30min. After the reaction is complete, cool to room temperature, centrifuge at 7000r / min in a high-speed centrifuge, and remove the supernatant. Wash the precipitate with 50mL of ethylene glycol ether and centrifuge, repeat three times. Place in an oven at 65 o C and dried for 12 h. The obtained olefin siloxane-modified nano-calcium carbonate was dispersed in 10 mL of N,N-dimethylformamide solution with 3 g of olefin siloxane-modified nano-calcium carbonate and stirred for 30 min. It was further dispersed by ultrasonic dispersion with a power of 200 W for 15 min. Then, 2 mL of acrylic acid-(di)-ethylene glycol ethyl ether ester, 0.3 mL of acrylic acid and 20 mg of azobisisobutyronitrile were added to the solution. The mixture was heated to 65 °C under nitrogen protection.o C for 3 h, then cool to room temperature, add 200 mL of industrial alcohol to quench the reaction and precipitate the product to obtain polyethylene glycol ethyl ether ester modified nano-calcium carbonate; wash with 50 mL of industrial alcohol and centrifuge; repeat three times to obtain polyethylene glycol ethyl ether ester modified nano-calcium carbonate.
[0053] Comparative Example 1 (Preparation of polymer-based thermochromic pigment, butyl acrylate is replaced by basic monomer 4-aminostyrene, and the pigment changes from red to blue-green)
[0054] Step 1, preparation of a polymerizable Ni-based thermochromic complex, specifically:
[0055] Take 5mL of acetylacetone and add it to 10mL of tetrahydrofuran solution. Add 1g of sodium carbonate and stir for 15min. Then add 4g of 4-vinylbenzyl chloride and separate through a column to obtain styryl acetylacetone. Take 1g of styryl acetylacetone, 0.7g of nickel nitrate, 0.8mL of N, N, N'-trimethylethylenediamine and 1.5g of sodium tetraphenylborate and add them to 20mL of ethanol solution respectively. Stir evenly and then add 20mL of 3mol / L sodium carbonate aqueous solution. Stir at room temperature for 20min, then filter to obtain a red filter cake, and wash it three times with 100mL of deionized water, 45 o C for 12 h to obtain a red monomer, i.e., a polymerizable Ni-based thermochromic complex.
[0056] Step 2, preparation of polymer-based thermochromic pigment, specifically:
[0057] Take 3g of polymerizable Ni-based thermochromic complex monomer and add it to 10mL of tetrahydrofuran solution. Then add 6mL of 4-aminostyrene, 4mL of glycidyl acrylate, and 0.3mL of glycerol triacrylate. Stir evenly, add 20mg of azobisisobutyronitrile and heat to 65℃ under nitrogen atmosphere. o C for 6 hours. After the reaction, the reaction solution was directly poured into 100 mL of industrial alcohol to quench the reaction and precipitate to obtain a blue-green powder, which was then washed three times with 100 mL of industrial alcohol to obtain a polymer-based thermochromic pigment.
[0058] Step 3, preparation of polymer-based thermochromic ink, specifically:
[0059] Take 2g of polymer-based thermochromic pigment, 5mL of ethylene glycol ethyl ether and 0.5g of starch, add them into a grinder and grind for 10min to obtain a gel-like ink, then continue to add 5mL of ethylene glycol ethyl ether solvent and 0.12g of cross-linking agent triphenylmethane triisocyanate, stir evenly to obtain a polymer-based thermochromic ink.
[0060] The ink is placed in an inkjet printer and sprayed on the glass surface containing the fast absorbing layer.
[0061] The preparation process of the fast absorption layer is as follows:
[0062] Take 2g of polyethylene glycol ethyl ether modified nano calcium carbonate, 0.2mL of acrylic acid, 0.5mL of acrylic acid-(di)-ethylene glycol ethyl ether and 3mL of ethanol, add them into a grinder and grind for 10 min to obtain a gel-like ink, then continue to add 3mL of ethanol solvent and 5mg of azobisisobutyronitrile, and spray the mixed solution on the glass surface with a thickness of 10um. Finally, 45W ultraviolet lamp is used for irradiation for 10s.
[0063] Wherein, the preparation process of polyethylene glycol ether ester modified nano calcium carbonate is:
[0064] Take 5 g of nano calcium carbonate and add it to 50 mL of ethylene glycol ether solvent, stir for 30 min, and further use 200 W ultrasonic disperser to ultrasonically disperse for 15 min to obtain nano calcium carbonate dispersion. o C, and add 2g of 3-(trimethoxysilyl) propyl methacrylate dropwise to the dispersion for 15min. Continue the reaction for 30min. After the reaction is complete, cool to room temperature, centrifuge at 7000r / min in a high-speed centrifuge, and remove the supernatant. Wash the precipitate with 50mL of ethylene glycol ether and centrifuge, repeat three times. Place in an oven at 65 o C and dried for 12 h. The obtained olefin siloxane-modified nano-calcium carbonate was dispersed in 10 mL of N,N-dimethylformamide solution with 3 g of olefin siloxane-modified nano-calcium carbonate and stirred for 30 min. It was further dispersed by ultrasonic dispersion with a power of 200 W for 15 min. Then, 2 mL of acrylic acid-(di)-ethylene glycol ethyl ether ester, 0.3 mL of acrylic acid and 20 mg of azobisisobutyronitrile were added to the solution. The mixture was heated to 65 °C under nitrogen protection. o C for 3 h, then cool to room temperature, add 200 mL of industrial alcohol to quench the reaction and precipitate the product to obtain polyethylene glycol ethyl ether ester modified nano-calcium carbonate; wash with 50 mL of industrial alcohol and centrifuge; repeat three times to obtain polyethylene glycol ethyl ether ester modified nano-calcium carbonate.
[0065] Comparative Example 2 (Preparation of polymer-based thermochromic pigment, butyl acrylate was replaced by acidic monomer acrylic acid, and the pigment changed from red to blue-green)
[0066] Step 1, preparation of a polymerizable Ni-based thermochromic complex, specifically:
[0067] Take 5mL of acetylacetone and add it to 10mL of tetrahydrofuran solution. Add 1g of sodium carbonate and stir for 15min. Then add 4g of 4-vinylbenzyl chloride and separate through a column to obtain styryl acetylacetone. Take 1g of styryl acetylacetone, 0.7g of nickel nitrate, 0.8mL of N, N, N'-trimethylethylenediamine and 1.5g of sodium tetraphenylborate and add them to 20mL of ethanol solution respectively. Stir evenly and then add 20mL of 3mol / L sodium carbonate aqueous solution. Stir at room temperature for 20min, then filter to obtain a red filter cake, and wash it three times with 100mL of deionized water, 45 o C for 12 h to obtain a red monomer, i.e., a polymerizable Ni-based thermochromic complex.
[0068] Step 2, preparation of polymer-based thermochromic pigment, specifically:
[0069] Take 3g of polymerizable Ni-based thermochromic complex monomer and add it to 10mL of tetrahydrofuran solution. Then add 6mL of acrylic acid, 4mL of glycidyl acrylate and 0.3mL of glycerol triacrylate and stir evenly. Then add 20mg of azobisisobutyronitrile and heat to 65℃ under nitrogen atmosphere. o C for 6 hours. After the reaction, the reaction solution was directly poured into 100 mL of industrial alcohol to quench the reaction and precipitate to obtain a blue-green powder, which was then washed three times with 100 mL of industrial alcohol to obtain a polymer-based thermochromic pigment.
[0070] Step 3, preparation of polymer-based thermochromic ink, specifically:
[0071] Take 2g of polymer-based thermochromic pigment, 5mL of ethylene glycol ethyl ether and 0.5g of starch, add them into a grinder and grind for 10min to obtain a gel-like ink, then continue to add 5mL of ethylene glycol ethyl ether solvent and 0.12g of cross-linking agent triphenylmethane triisocyanate, stir evenly to obtain a polymer-based thermochromic ink.
[0072] The ink is placed in an inkjet printer and sprayed on the glass surface containing the fast absorbing layer.
[0073] The preparation process of the fast absorption layer is as follows:
[0074] Take 2g of polyethylene glycol ethyl ether modified nano calcium carbonate, 0.2mL of acrylic acid, 0.5mL of acrylic acid-(di)-ethylene glycol ethyl ether, and 3mL of ethanol, add them into a grinder and grind for 10 min to obtain a gel-like ink, then continue to add 3mL of ethanol solvent and 5mg of azobisisobutyronitrile, and spray the mixed solution on the glass surface with a thickness of 10um. Finally, 45W ultraviolet lamp is used for irradiation for 10s.
[0075] Comparative Example 3 (Polymer-based thermochromic pigment replaced with Ni-based thermochromic complex crystal, nozzle blocked)
[0076] Step 1, preparation of Ni-based thermochromic complex, specifically:
[0077] Take 1g of acetylacetone, 0.7g of nickel nitrate, 0.8mL of N, N, N'-trimethylethylenediamine and 1.5g of sodium tetraphenylborate and add them to 20mL of ethanol solution, stir evenly and then add 20mL of 3mol / L sodium carbonate aqueous solution. Stir at room temperature for 20min, then filter to get a red filter cake, and wash it three times with 100mL of deionized water, 45 o C for 12 h to obtain red complex crystals, namely, Ni-based thermochromic complex.
[0078] Step 2, preparation of polymer-based thermochromic ink, specifically:
[0079] Take 2g of Ni-based thermochromic complex pigment, 5mL of ethylene glycol ethyl ether and 0.5g of starch, add them into a grinder and grind for 10 min to obtain a gel-like ink, then continue to add 5mL of ethylene glycol ethyl ether solvent and 0.12g of cross-linking agent triphenylmethane triisocyanate, stir evenly to obtain a polymer-based thermochromic ink.
[0080] The ink is placed in an inkjet printer and sprayed on the glass surface containing the fast absorbing layer.
[0081] The preparation process of the fast absorption layer is as follows:
[0082] Take 2g of polyethylene glycol ethyl ether modified nano calcium carbonate, 0.2mL of acrylic acid, 0.5mL of acrylic acid-(di)-ethylene glycol ethyl ether and 3mL of ethanol, add them into a grinder and grind for 10 min to obtain a gel ink, then continue to add 3mL of ethanol solvent and 5mg of azobisisobutyronitrile, and spray the mixed solution on the glass surface with a thickness of 10um. Finally, 45W ultraviolet lamp is used for irradiation for 10s.
[0083] Wherein, the preparation process of polyethylene glycol ether ester modified nano calcium carbonate is:
[0084] Take 5 g of nano calcium carbonate and add it to 50 mL of ethylene glycol ether solvent, stir for 30 min, and further use 200 W ultrasonic disperser to ultrasonically disperse for 15 min to obtain nano calcium carbonate dispersion. oC, and add 2g of 3-(trimethoxysilyl) propyl methacrylate dropwise to the dispersion for 15min. Continue the reaction for 30min. After the reaction is complete, cool to room temperature, centrifuge at 7000r / min in a high-speed centrifuge, and remove the supernatant. Wash the precipitate with 50mL of ethylene glycol ether and centrifuge, repeat three times. Place in an oven at 65 o C and dried for 12 h. The obtained olefin siloxane-modified nano-calcium carbonate was dispersed in 10 mL of N,N-dimethylformamide solution with 3 g of olefin siloxane-modified nano-calcium carbonate and stirred for 30 min. It was further dispersed by ultrasonic dispersion with a power of 200 W for 15 min. Then, 2 mL of acrylic acid-(di)-ethylene glycol ethyl ether ester, 0.3 mL of acrylic acid and 20 mg of azobisisobutyronitrile were added to the solution. The mixture was heated to 65 °C under nitrogen protection. o C for 3 h, then cool to room temperature, add 200 mL of industrial alcohol to quench the reaction and precipitate the product to obtain polyethylene glycol ethyl ether ester modified nano-calcium carbonate; wash with 50 mL of industrial alcohol and centrifuge; repeat three times to obtain polyethylene glycol ethyl ether ester modified nano-calcium carbonate.
[0085] Comparative Example 4 (When the ink was sprayed, the substrate was not treated with a quick absorption layer and the ink could not dry)
[0086] Step 1, preparation of a polymerizable Ni-based thermochromic complex, specifically:
[0087] Take 5mL of acetylacetone and add it to 10mL of tetrahydrofuran solution. Add 1g of sodium carbonate and stir for 15min. Then add 4g of 4-vinylbenzyl chloride and separate through a column to obtain styryl acetylacetone. Take 1g of styryl acetylacetone, 0.7g of nickel nitrate, 0.8mL of N, N, N'-trimethylethylenediamine and 1.5g of sodium tetraphenylborate and add them to 20mL of ethanol solution respectively. Stir evenly and then add 20mL of 3mol / L sodium carbonate aqueous solution. Stir at room temperature for 20min, then filter to obtain a red filter cake, and wash it three times with 100mL of deionized water, 45 o C for 12 h to obtain a red monomer, i.e., a polymerizable Ni-based thermochromic complex.
[0088] Step 2, preparation of polymer-based thermochromic pigment, specifically:
[0089] Take 3g of polymerizable Ni-based thermochromic complex monomer and add it to 10mL of tetrahydrofuran solution. Then add 6mL of butyl acrylate, 4mL of glycidyl acrylate and 0.3mL of glyceryl triacrylate, stir evenly, add 20mg of azobisisobutyronitrile and heat to 65℃ under nitrogen atmosphere. oC for 6 hours. After the reaction, the reaction solution was directly poured into 100 mL of industrial alcohol to quench the reaction and precipitate to obtain a red powder, which was then washed three times with 100 mL of industrial alcohol to obtain a polymer-based thermochromic pigment.
[0090] Step 3, preparation of polymer-based thermochromic ink, specifically:
[0091] 2g of polymer-based thermochromic pigment, 5mL of ethylene glycol ethyl ether and 0.5g of starch were added to a grinder and ground for 10 minutes to obtain a gel ink, and 5mL of ethylene glycol ethyl ether solvent and 0.12g of triphenylmethane triisocyanate, a cross-linking agent, were added and stirred to obtain a polymer-based thermochromic ink. The ink was placed in an inkjet printer and sprayed on the glass surface.
[0092] Comparative Example 5 (the absorption layer was treated without adding polyethylene glycol ether ester modified nano calcium carbonate, and the ink could not dry)
[0093] Step 1, preparation of a polymerizable Ni-based thermochromic complex, specifically:
[0094] Take 5mL of acetylacetone and add it to 10mL of tetrahydrofuran solution. Add 1g of sodium carbonate and stir for 15min. Then add 4g of 4-vinylbenzyl chloride and separate through a column to obtain styryl acetylacetone. Take 1g of styryl acetylacetone, 0.7g of nickel nitrate, 0.8mL of N, N, N'-trimethylethylenediamine and 1.5g of sodium tetraphenylborate and add them to 20mL of ethanol solution respectively. Stir evenly and then add 20mL of 3mol / L sodium carbonate aqueous solution. Stir at room temperature for 20min, then filter to obtain a red filter cake, and wash it three times with 100mL of deionized water, 45 o C for 12 h to obtain a red monomer, i.e., a polymerizable Ni-based thermochromic complex.
[0095] Step 2, preparation of polymer-based thermochromic pigment, specifically:
[0096] Take 3g of polymerizable Ni-based thermochromic complex monomer and add it to 10mL of tetrahydrofuran solution. Then add 6mL of butyl acrylate, 4mL of glycidyl acrylate and 0.3mL of glyceryl triacrylate, stir evenly, add 20mg of azobisisobutyronitrile and heat to 65℃ under nitrogen atmosphere. o C for 6 hours. After the reaction, the reaction solution was directly poured into 100 mL of industrial alcohol to quench the reaction and precipitate to obtain a red powder, which was then washed three times with 100 mL of industrial alcohol to obtain a polymer-based thermochromic pigment.
[0097] Step 3, preparation of polymer-based thermochromic ink, specifically:
[0098] Take 2g of polymer-based thermochromic pigment, 5mL of ethylene glycol ethyl ether and 0.5g of starch, add them into a grinder and grind for 10min to obtain a gel-like ink, then continue to add 5mL of ethylene glycol ethyl ether solvent and 0.12g of cross-linking agent triphenylmethane triisocyanate, stir evenly to obtain a polymer-based thermochromic ink.
[0099] The ink is placed in an inkjet printer and sprayed on the glass surface containing the fast absorbing layer.
[0100] The preparation process of the fast absorption layer is as follows:
[0101] Take 0.2mL of acrylic acid, 0.5mL of acrylic acid-(di)-ethylene glycol ethyl ether ester and 3mL of ethanol, add them into a grinder and grind for 10 min to obtain an oily ink. Continue to add 3mL of ethanol solvent and 5mg of azobisisobutyronitrile. Spray the mixed solution on the glass surface with a thickness of 10um. Finally, irradiate with a 45W ultraviolet lamp for 10s.
[0102] Comparative Example 6 (The solvent ethylene glycol ethyl ether in the polymer-based thermochromic ink was replaced with toluene, and the ink could not dry)
[0103] Step 1, preparation of a polymerizable Ni-based thermochromic complex, specifically:
[0104] Take 5mL of acetylacetone and add it to 10mL of tetrahydrofuran solution. Add 1g of sodium carbonate and stir for 15min. Then add 4g of 4-vinylbenzyl chloride and separate through a column to obtain styryl acetylacetone. Take 1g of styryl acetylacetone, 0.7g of nickel nitrate, 0.8mL of N, N, N'-trimethylethylenediamine and 1.5g of sodium tetraphenylborate and add them to 20mL of ethanol solution respectively. Stir evenly and then add 20mL of 3mol / L sodium carbonate aqueous solution. Stir at room temperature for 20min, then filter to obtain a red filter cake, and wash it three times with 100mL of deionized water, 45 o C for 12 h to obtain a red monomer, i.e., a polymerizable Ni-based thermochromic complex.
[0105] Step 2, preparation of polymer-based thermochromic pigment, specifically:
[0106] Take 3g of polymerizable Ni-based thermochromic complex monomer and add it to 10mL of tetrahydrofuran solution. Then add 6mL of butyl acrylate, 4mL of glycidyl acrylate and 0.3mL of glyceryl triacrylate, stir evenly, add 20mg of azobisisobutyronitrile and heat to 65℃ under nitrogen atmosphere. o C for 6 hours. After the reaction, the reaction solution was directly poured into 100 mL of industrial alcohol to quench the reaction and precipitate to obtain a red powder, which was then washed three times with 100 mL of industrial alcohol to obtain a polymer-based thermochromic pigment.
[0107] Step 3, preparation of polymer-based thermochromic ink, specifically:
[0108] Take 2g of polymer-based thermochromic pigment, 5mL of toluene and 0.5g of starch and add them to a grinder and grind for 10 min to obtain a gel ink, then add 5mL of toluene solvent and 0.12g of triphenylmethane triisocyanate, a cross-linking agent, and stir evenly to obtain a polymer-based thermochromic ink. Put the ink into an inkjet printer and spray it on the glass surface with a fast absorption layer.
[0109] The preparation process of the fast absorption layer is as follows:
[0110] Take 2g of polyethylene glycol ethyl ether modified nano calcium carbonate, 0.2mL of acrylic acid, 0.5mL of acrylic acid-(di)-ethylene glycol ethyl ether and 3mL of ethanol, add them into a grinder and grind for 10 min to obtain a gel ink, then continue to add 3mL of ethanol solvent and 5mg of azobisisobutyronitrile, and spray the mixed solution on the glass surface with a thickness of 10um. Finally, 45W ultraviolet lamp is used for irradiation for 10s.
[0111] Wherein, the preparation process of polyethylene glycol ether ester modified nano calcium carbonate is:
[0112] Take 5 g of nano calcium carbonate and add it to 50 mL of ethylene glycol ether solvent, stir for 30 min, and further use 200 W ultrasonic disperser to ultrasonically disperse for 15 min to obtain nano calcium carbonate dispersion. o C, and add 2g of 3-(trimethoxysilyl) propyl methacrylate dropwise to the dispersion for 15min. Continue the reaction for 30min. After the reaction is complete, cool to room temperature, centrifuge at 7000r / min in a high-speed centrifuge, and remove the supernatant. Wash the precipitate with 50mL of ethylene glycol ether and centrifuge, repeat three times. Place in an oven at 65 o C and dried for 12 h. The obtained olefin siloxane-modified nano-calcium carbonate was dispersed in 10 mL of N,N-dimethylformamide solution with 3 g of olefin siloxane-modified nano-calcium carbonate and stirred for 30 min. It was further dispersed by ultrasonic dispersion with a power of 200 W for 15 min. Then, 2 mL of acrylic acid-(di)-ethylene glycol ethyl ether ester, 0.3 mL of acrylic acid and 20 mg of azobisisobutyronitrile were added to the solution. The mixture was heated to 65 °C under nitrogen protection. o C for 3 h, then cool to room temperature, add 200 mL of industrial alcohol to quench the reaction and precipitate the product to obtain polyethylene glycol ethyl ether ester modified nano-calcium carbonate; wash with 50 mL of industrial alcohol and centrifuge; repeat three times to obtain polyethylene glycol ethyl ether ester modified nano-calcium carbonate.
[0113] Results and Discussion
[0114] Table 1 Pigment properties and characterization
[0115] Pigment color (room temperature) Maximum absorption peak (room temperature) <![CDATA[Pigment color (80 o C)]]> <![CDATA[Maximum absorption peak (80 o °C)]]> Example 1 red 485 nm blue 582 nm Comparative Example 1 Teal 600 nm / / Comparative Example 2 Teal 600 nm / / Comparative Example 3 red 485 nm blue 582 nm Comparative Example 4 red 485 nm blue 582 nm Comparative Example 5 red 485 nm blue 582 nm Comparative Example 6 red 485 nm blue 582 nm
[0116] like Figure 1 As shown in Table 1, the maximum absorption peak position of Example 1 at room temperature is 485nm, the peak type is broad, and the pigment color is red. When the pigment is heated to , the maximum absorption peak changes to 600nm, which is also a broad peak, and the corresponding pigment color is blue. It has a thermochromic change from red (room temperature) to blue (heating).
[0117] In the preparation of the polymer-based thermochromic pigment of Comparative Example 1, butyl acrylate was replaced with the basic monomer 4-aminostyrene, and the pigment changed from red to blue-green. This is because the ligand N, N, N'-trimethylethylenediamine in the molecular structure of the polymer-based thermochromic pigment contains an amine functional group, and the 4-aminostyrene monomer also contains an amine group, which destroys the original pigment structure. As a result, the color of the pigment changes and there is no thermochromic property.
[0118] In the preparation of the polymer-based thermochromic pigment of Comparative Example 2, butyl acrylate was replaced with an acidic monomer acrylic acid, and the pigment changed from red to blue-green. This is because acrylic acid is an acidic monomer, and the acid causes the coordination structure of Ni in the pigment molecule to decompose, and the carboxyl group forms a bidentate chelate with the Ni ion, resulting in the destruction of the pigment structure and the lack of thermochromic properties.
[0119] In Comparative Examples 3-6, the pigments all show thermochromic properties, and the color change of the pigments is from red at room temperature to blue when heated.
[0120] Example 1 and Comparative Examples 1-2, 4-6 all show shear thinning behavior of polymers. In Comparative Example 3, Ni-based thermochromic complex crystals were added, and the test results had large errors, so no results were given.
[0121] Comparative Example 3, the polymer-based thermochromic pigment is replaced with a Ni-based thermochromic complex crystal, and the nozzle is blocked, as shown in Table 2. This is because the polymer-based thermochromic pigment polymerizes the small molecule complex through free radical polymerization, and the small molecule complex pigment and a variety of different types of polymerization monomers are polymerized and randomly polymerized at the same time, and the entire polymer skeleton is an amorphous configuration (non-crystalline, X-ray powder diffraction results show that the 2θ diffraction angle is 10-20 oNo sharp diffraction peaks appear, only a broad peak of amorphous polymer), and the pigment complex monomers are randomly distributed in the polymer skeleton, which solves the problem of crystallization of the complex. On the contrary, the Ni-based thermochromic complex crystals are easy to crystallize, and their crystal particle size is millimeter-level, which is much larger than the aperture of the inkjet printing head (micrometer-level), and cannot be printed. On the contrary, the pigment molecules used in Example 1 and Comparative Examples 1-2, 4-6 are all polymer-based and can be printed.
[0122] In comparative example 4, when the ink was sprayed, the substrate was not treated with a quick absorption layer and was directly sprayed on the glass surface, and the ink could not dry. As we all know, the ink can dry quickly when sprayed on the surface of traditional paper because the paper has been treated with surface sizing to enhance the ink absorption performance. However, the glass is dense and the ink cannot penetrate. The prepared ink solvent is ethylene glycol ether, which has a boiling point of up to 135 o C, difficult to volatilize, as shown in Table 2.
[0123] In comparative example 5, the absorption layer was treated without adding polyethylene glycol ether ester modified nano calcium carbonate, and the ink could not be dried. This is because nano calcium carbonate has a porous structure and acts as an ink solvent adsorbent, so Example 1 and comparative examples 1-2 are very easy to dry. However, comparative example 5 could not be dried.
[0124] In Comparative Example 6, the solvent ethylene glycol ether in the polymer-based thermochromic ink was replaced with toluene, and the ink could not dry. The surface of the nano-calcium carbonate in Example 1 and Comparative Examples 1-2 was modified by polyethylene glycol ether ester, and polyethylene glycol ether ester and the ink solvent ethylene glycol ether had similar physical properties, and were easily compatible and penetrated into the nano-calcium carbonate. In Comparative Example 6, the ink solvent was toluene, which was lipophilic and had poor compatibility with the polyethylene glycol ether ester on the surface of the nano-calcium carbonate, and the nano-calcium carbonate was hydrophilic and immiscible with the lipophilic toluene. As a result, toluene could not enter the nano-calcium carbonate, and the ink was difficult to dry.
[0125] Table 2 Inkjet printing performance of ink
[0126] Rheology Sprayability Drying time after ink spraying (room temperature) Example 1 Shear Thinning Can 10s Comparative Example 1 Shear Thinning Can 10s Comparative Example 2 Shear Thinning Can 10s Comparative Example 3 / no / Comparative Example 4 Shear Thinning Can 8min Comparative Example 5 Shear Thinning Can 8min Comparative Example 6 Shear Thinning Can 8min
[0127] Example 2
[0128] Step 1, preparation of a polymerizable Ni-based thermochromic complex, specifically:
[0129] Take 8 mL of acetylacetone and add it to 12 mL of tetrahydrofuran solution. Add 1.5 g of sodium carbonate and stir for 25 min. Then add 7 g of 4-vinylbenzyl chloride and separate through a column to obtain styryl acetylacetone. Take 1.5 g of styryl acetylacetone, 1.2 g of nickel nitrate, 1.2 mL of N, N, N'-trimethylethylenediamine and 2 g of sodium tetraphenylborate and add them to 30 mL of ethanol solution respectively. Stir evenly and then add 30 mL of 4 mol / L sodium carbonate aqueous solution. Stir at room temperature for 30 min, then filter to obtain a red filter cake, and wash it three times with 150 mL of deionized water, 55 o C for 18 h to obtain a red monomer, i.e., a polymerizable Ni-based thermochromic complex.
[0130] Step 2, preparation of polymer-based thermochromic pigment, specifically:
[0131] Take 4g of polymerizable Ni-based thermochromic complex monomer and add it to 15mL of tetrahydrofuran solution. Then add 10mL of butyl acrylate, 7mL of glycidyl acrylate and 0.4mL of glyceryl triacrylate, stir evenly, add 25mg of azobisisobutyronitrile and heat to 75℃ under nitrogen atmosphere. o C for 8 hours. After the reaction, the reaction solution was directly poured into 150 mL of industrial alcohol to quench the reaction and precipitate to obtain a red powder, which was then washed three times with 150 mL of industrial alcohol to obtain a polymer-based thermochromic pigment.
[0132] Step 3, preparation of polymer-based thermochromic ink, specifically:
[0133] Take 3g of polymer-based thermochromic pigment, 8mL of ethylene glycol ethyl ether and 0.8g of starch, add them into a grinder and grind for 15min to obtain a gel-like ink, continue to add 8mL of ethylene glycol ethyl ether solvent and 0.18g of cross-linking agent triphenylmethane triisocyanate, stir evenly to obtain a polymer-based thermochromic ink.
[0134] The ink is placed in an inkjet printer and sprayed on the glass surface containing the fast absorbing layer.
[0135] The preparation process of the fast absorption layer is as follows:
[0136] Take 3g of polyethylene glycol ethyl ether modified nano calcium carbonate, 0.3mL of acrylic acid, 0.8mL of acrylic acid-(di)-ethylene glycol ethyl ether and 4mL of ethanol, add them into a grinder and grind for 15min to obtain a gel-like ink, then continue to add 4mL of ethanol solvent and 8mg of azobisisobutyronitrile, and spray the mixed solution on the glass surface with a thickness of 15um. Finally, 55W ultraviolet lamp is used for irradiation for 12s.
[0137] Wherein, the preparation process of polyethylene glycol ether ester modified nano calcium carbonate is:
[0138] Take 8 g of nano calcium carbonate and add it to 80 mL of ethylene glycol ether solvent, stir for 40 min, and further use 300 W ultrasonic disperser to ultrasonically disperse for 20 min to obtain nano calcium carbonate dispersion. Heat the dispersion to 70 o C, and add 2.5g of 3-(trimethoxysilyl) propyl methacrylate dropwise to the dispersion for 25min. Continue the reaction for 40min. After the reaction is complete, cool to room temperature, centrifuge at 9000r / min in a high-speed centrifuge, and remove the supernatant. Wash the precipitate with 80mL of ethylene glycol ether and centrifuge, repeat three times. Place in an oven at 75 o C and dried for 18 h. 5 g of the obtained olefin siloxane-modified nano-calcium carbonate was dispersed in 15 mL of N,N-dimethylformamide solution and stirred for 40 min. Ultrasonic dispersion was further performed for 25 min using a 300 W ultrasonic disperser. Then, 3 mL of acrylic acid-(di)-ethylene glycol ethyl ether ester, 0.4 mL of acrylic acid and 30 mg of azobisisobutyronitrile were added to the solution. The mixture was heated to 70°C under nitrogen protection. o C for 4 h, then cool to room temperature, add 300 mL of industrial alcohol to quench the reaction and precipitate the product to obtain polyethylene glycol ethyl ether ester modified nano-calcium carbonate, wash it in 80 mL of industrial alcohol, and centrifuge it. Repeat this process three times to obtain polyethylene glycol ethyl ether ester modified nano-calcium carbonate.
[0139] Example 3
[0140] Step 1, preparation of a polymerizable Ni-based thermochromic complex, specifically:
[0141] Take 10 mL of acetylacetone and add it to 15 mL of tetrahydrofuran solution. Add 2 g of sodium carbonate and stir for 30 min. Then add 8 g of 4-vinylbenzyl chloride and separate through a column to obtain styryl acetylacetone. Take 2 g of styryl acetylacetone, 1.4 g of nickel nitrate, 1.6 mL of N, N, N'-trimethylethylenediamine and 3 g of sodium tetraphenylborate and add them to 40 mL of ethanol solution respectively. Stir evenly and then add 40 mL of 6 mol / L sodium carbonate aqueous solution. Stir at room temperature for 40 min, then filter to obtain a red filter cake, and wash it three times with 200 mL of deionized water and 60 o C for 24 h to obtain a red monomer, i.e., a polymerizable Ni-based thermochromic complex.
[0142] Step 2, preparation of polymer-based thermochromic pigment, specifically:
[0143] Take 6 g of polymerizable Ni-based thermochromic complex monomer and add it to 20 mL of tetrahydrofuran solution. Then add 12 mL of butyl acrylate, 8 mL of glycidyl acrylate, and 0.6 mL of glycerol triacrylate. Stir evenly, add 30 mg of azobisisobutyronitrile, and heat to 80 °C under nitrogen atmosphere. o C for 12 hours. After the reaction, the reaction solution was directly poured into 200 mL of industrial alcohol to quench the reaction and precipitate to obtain a red powder, which was then washed three times with 200 mL of industrial alcohol to obtain a polymer-based thermochromic pigment.
[0144] Step 3, preparation of polymer-based thermochromic ink, specifically:
[0145] Take 4g of polymer-based thermochromic pigment, 10mL of ethylene glycol ethyl ether and 1g of starch, add them into a grinder and grind for 20min to obtain a gel-like ink, continue to add 10mL of ethylene glycol ethyl ether solvent and 0.24g of cross-linking agent triphenylmethane triisocyanate, stir evenly to obtain a polymer-based thermochromic ink.
[0146] The ink is placed in an inkjet printer and sprayed on the glass surface containing the fast absorbing layer.
[0147] The preparation process of the fast absorption layer is as follows:
[0148] Take 4g of polyethylene glycol ethyl ether modified nano calcium carbonate, 0.4mL of acrylic acid, 1mL of acrylic acid-(di)-ethylene glycol ethyl ether and 6mL of ethanol, add them into a grinder and grind for 20min to obtain a gel ink, then continue to add 6mL of ethanol solvent and 10mg of azobisisobutyronitrile, and spray the mixed solution on the glass surface with a thickness of 20um. Finally, irradiate with a 60W ultraviolet lamp for 15s.
[0149] Wherein, the preparation process of polyethylene glycol ether ester modified nano calcium carbonate is:
[0150] Take 10 g of nano calcium carbonate and add it to 100 mL of ethylene glycol ether solvent, stir for 60 min, and further use a 400 W ultrasonic disperser to ultrasonically disperse for 30 min to obtain a nano calcium carbonate dispersion. Heat the dispersion to 80 o C, and add 3g of 3-(trimethoxysilyl) propyl methacrylate dropwise to the dispersion for 30min. Continue the reaction for 60min after the addition is complete. After the reaction is complete, cool to room temperature, centrifuge at 10000r / min using a high-speed centrifuge, and remove the supernatant. Wash the precipitate with 100mL of ethylene glycol ether and centrifuge, repeat three times. Place in an oven at 80 oC and dried for 24 h. 6 g of the obtained olefin siloxane-modified nano-calcium carbonate was dispersed in 20 mL of N,N-dimethylformamide solution and stirred for 60 min. Ultrasonic dispersion was further performed for 30 min using a 400 W ultrasonic disperser. Then, 4 mL of acrylic acid-(di)-ethylene glycol ethyl ether ester, 0.6 mL of acrylic acid and 40 mg of azobisisobutyronitrile were added to the solution. The mixture was heated to 80 °C under nitrogen protection. o C for 6h, cool to room temperature, add 400mL of industrial alcohol to quench the reaction and precipitate the product to obtain polyethylene glycol ethyl ether ester modified nano calcium carbonate, wash it in 100mL of industrial alcohol, and centrifuge it. Repeat this process three times to obtain polyethylene glycol ethyl ether ester modified nano calcium carbonate.
Claims
1. A method for preparing a thermochromic ink for inkjet printing, characterized in that: The specific steps include: Step 1, preparing a polymerizable Ni-based thermochromic complex; Step 2, preparing a polymer-based thermochromic pigment based on the product obtained in step 1; Step 3, preparing a polymer-based thermochromic ink based on the product obtained in step 2, The specific process of step 1 is as follows: Step 1.1, add 5-10 mL of acetylacetone to 10-15 mL of tetrahydrofuran solution, then add 1-2 g of sodium carbonate and stir for 15-30 min, then add 4-8 g of 4-vinylbenzyl chloride, and separate through a column to obtain styryl acetylacetone; Step 1.2, take 1-2g of styryl acetylacetone, 0.7-1.4g of nickel nitrate, 0.8-1.6mL of N, N, N'-trimethylethylenediamine and 1.5-3g of sodium tetraphenylborate, add them to 20-40mL of ethanol solution respectively, stir evenly, then add 20-40mL of 3-6mol / L sodium carbonate aqueous solution, stir at room temperature for 20-40min, then filter to obtain a red filter cake, wash it three times with 100-200mL of deionized water, dry it at 45-60℃ for 12-24h, and obtain a red monomer, that is, a polymerizable Ni-based thermochromic complex monomer; The specific process of step 2 is as follows: Take 3-6g of polymerizable Ni-based thermochromic complex monomer, add it to 10-20mL of tetrahydrofuran solution, then add 6-12mL of butyl acrylate, 4-8mL of glycidyl acrylate, and 0.3-0.6mL of triacrylate glycerol in sequence, stir evenly, add 20-30mg of azobisisobutyronitrile, heat to 65-80℃ under nitrogen atmosphere for 6-12h, after the reaction is completed, pour the reaction solution directly into 100-200mL of industrial alcohol to quench the reaction and precipitate to obtain red powder, continue to wash with 100-200mL of industrial alcohol repeatedly for 3 times to obtain a polymer-based thermochromic pigment; The specific process of step 3 is as follows: 2-4 g of a polymer-based thermochromic pigment, 5-10 mL of ethylene glycol ethyl ether and 0.5-1 g of starch are added to a grinder and ground for 10-20 min to obtain a gel-like ink, and 5-10 mL of ethylene glycol ethyl ether solvent and 0.12-0.24 g of triphenylmethane triisocyanate are added, and stirred evenly to obtain a polymer-based thermochromic ink.
2. Inkjet printing thermochromic ink, characterized in that: The invention is prepared by the method for preparing the thermochromic ink for inkjet printing according to claim 1.
3. The inkjet printing thermochromic ink according to claim 2, which is used for spraying on glass.
4. The thermochromic ink for inkjet printing according to claim 3, characterized in that: Before spraying ink on the glass, an absorbent layer must first be sprayed on the glass surface.
5. The thermochromic ink for inkjet printing according to claim 4, characterized in that: The preparation process of the absorption layer is as follows: 2-4g of polyethylene glycol ethyl ether ester modified nano calcium carbonate, 0.2-0.4mL of acrylic acid, 0.5-1mL of acrylic acid-(di)-ethylene glycol ethyl ether ester and 3-6mL of ethanol are added into a grinder and ground for 10-20 minutes to obtain a gel ink, 3-6mL of ethanol solvent and 5-10mg of azobisisobutyronitrile are added to obtain a mixed solution; the mixed solution is sprayed on a glass surface to a thickness of 10-20um, and finally irradiated with a 45-60W ultraviolet lamp for 10-15s to obtain the obtained solution.
6. The thermochromic ink for inkjet printing according to claim 5, characterized in that: The preparation process of the polyethylene glycol ether ester modified nano calcium carbonate is as follows: 5-10 g of nano calcium carbonate is added to 50-100 mL of ethylene glycol ethyl ether solvent, stirred for 30-60 min, and ultrasonically dispersed for 15-30 min using an ultrasonic disperser with a power of 200-400 W to obtain a nano calcium carbonate dispersion; the nano calcium carbonate dispersion is heated to 60-80° C., and 2-3 g of 3-(trimethoxymethylsilyl)propyl methacrylate is dropwise added to the dispersion for 15-30 min. After the dropwise addition is completed, the reaction is continued for 30-60 min. After the reaction is completed, the mixture is cooled to room temperature, centrifuged at 7000-10000 r / min using a centrifuge, and the supernatant is removed; the precipitate is washed with 50-100 mL of ethylene glycol ethyl ether and centrifuged, the process is repeated three times, and the mixture is placed in an oven at 65-80° C. and dried for 12-24 h to obtain an olefin siloxane-modified nano calcium carbonate powder; Take 3-6g of olefin siloxane modified nano calcium carbonate powder and disperse it in N,N-dimethylformamide solution, stir for 30-60 min, use 200-400W ultrasonic disperser to ultrasonically disperse for 15-30 min, then add 2-4mL of acrylic acid-(di)-ethylene glycol ethyl ether ester, 0.3-0.6mL of acrylic acid and 20-40mg of azobisisobutyronitrile to the solution, heat to 65-80℃ under nitrogen protection for 3-6h, cool to room temperature, add 200-400mL of industrial alcohol to quench the reaction and precipitate the product, wash with 50-100mL of industrial alcohol, centrifuge, repeat three times to obtain polyethylene glycol ethyl ether ester modified nano calcium carbonate.
Citation Information
Patent Citations
Preparation method and curing method of deep curing and photochromic ink
CN119019888A
Thermochromic materials
GB1405701A